2015
DOI: 10.1021/acs.jpcc.5b03905
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Excited-State Dynamics of Diketopyrrolopyrrole (DPP)-Based Materials: Static versus Diffusion-Controlled Electron Transfer Process

Abstract: Singlet-to-triplet intersystem crossing (ISC) and photoinduced electron transfer (PET) of platinum(II)-containing diketopyrrolopyrrole (DPP) oligomers in the presence and absence of tetracyanoethylene (TCNE), a strong electron-acceptor, were investigated using femtosecond and nanosecond transient absorption spectroscopy with broadband capabilities. The effect of incorporating platinum(II) in the photophysical properties of DPP molecule was evaluated by comparing the excited-state dynamics of DPP with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
(111 reference statements)
2
14
0
Order By: Relevance
“…Hence, that FRET induced a decrease of DPP fluorescence due to acidochromic effect can safely be ruled out and decrease of DPP fluorescence could be rationalized by electron transfer from excited DPP to the 3 H -indolium cation. Indeed, the photoinduced electron transfer process in this case is highly exoergonic and the Gibbs free energy (Δ G 0 ) is broadly estimated to be ∼−0.8 eV considering the reduction potential of the 3 H -indolium (∼0.8 eV), oxidation potential, and excited singlet-state energy of DPP­(6) (∼0.8 eV and 2.4 eV (605 nm), respectively).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Hence, that FRET induced a decrease of DPP fluorescence due to acidochromic effect can safely be ruled out and decrease of DPP fluorescence could be rationalized by electron transfer from excited DPP to the 3 H -indolium cation. Indeed, the photoinduced electron transfer process in this case is highly exoergonic and the Gibbs free energy (Δ G 0 ) is broadly estimated to be ∼−0.8 eV considering the reduction potential of the 3 H -indolium (∼0.8 eV), oxidation potential, and excited singlet-state energy of DPP­(6) (∼0.8 eV and 2.4 eV (605 nm), respectively).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Besides on the linear platinum acetylides comprising photovoltaic materials, heavy metal organometallic polymers containing cyclometalated Pt or Ir complexes which was attached via the C^N or O^O diketonate ligands have been attracted gradually increasing attention due to better involvement from the orbitals of Pt or Ir center and the cyclometalated organic ligand to polymer backbone in both the ground and the excited states of the material [71][72][73][74][75]. Strong spin-orbit coupling on the heave metal center allows for the mixing of singlet metal-to-ligand charge transfer state ( 1 MLCT) with the formally forbidden triplet metal-to-ligand charge transfer ( 3 MCLT) and 3 π-π* states.…”
Section: Cyclometalated Pt/ir Complex Containing π-Conjugated Polymersmentioning
confidence: 99%
“…Together with the close lowest unoccupied molecular orbital (LUMO) (∼4.2 eV) of the polymer to that of PCBM which lead comparatively low driving force for charge separation at the donor-acceptor interface, BHJ photovoltaic device performed a rather low PCE of 0.22%. Besides on the cycloplatinated polymers, oligomers (40)(41)(42) of cyclometalated platinum complex by introducing the widely reported high performance diketopyrrolopyrrole (DPP) or Isoindigo (IID) moiety were also reported [71,74,75]. For example, when DPP chromophores were end-functionalized with platinum containing auxochromes, photophysics study revealed that compared with the platinum acetylide units, orthometalated platinum auxochrome 40 is more likely to induce a greater extent of spin-orbit coupling.…”
Section: Cyclometalated Pt/ir Complex Containing π-Conjugated Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoinduced charge transfer remains one of the most important photochemical reactions in chemistry, biology, and materials science. The process is usually characterized by the transfer of an electron from a photoexcited donor to an acceptor and is often driven by complex formations between the donor–acceptor moieties, especially if they carry opposite electrostatic charges. Such excited-state processes are significantly influenced by the properties of the solvents, including polarity and hydrogen-bonding interactions. For instance, time-resolved laser spectroscopic measurements in pico- and femtosecond time domains have been used to investigate the dynamics of hydrogen bonding in the excited singlet (S 1 ) state of ketone molecules in alcoholic solvents, where evolution of the excited-state properties has been observed and attributed to repositioning of the hydrogen bonds around the carbonyl group.…”
mentioning
confidence: 99%